Outcomes of percutaneous drainage without surgery for patients with diverticular abscess - Faisal, Elagili; Luca, Stocchi; Gokhan, Ozuner; David W, Dietz; Ravi P, Kiran (Wolters Kluwer, 2014)
BACKGROUND: Data on percutaneous drainage followed by observation for diverticular abscess is scant.